A Case of Hemorrhagic Shock for a Ruptured Splenic Aneurysm Treated With REBOA-Assisted Surgery - Chiara D’Alterio; Cristina Carruezzo; Armando Raso; Arezia Di Martino; Roberto Santoro; Domenico Giannotti (Case Reports in Surgery)
Conclusion: REBOA provides a rapid and minimally invasive hemodynamic control in severe hemorrhagic settings and its application in the initial management of nontraumatic abdominal hemorrhage should be strongly advised. Further studies with large sample size focusing on nontrauma patients are needed.